FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK UMKM DI WILAYAH NGEMPLAK - Ayu Fhatonah,; Astuning Saharsini, (Juremi: Jurnal Riset Ekonomi, 2022)
The problem underlying the reserch is the low awarenes, attitude, knowledge and understanding of tax sanctions which results in low tax compliance for MSMEs in the Ngemplak Region. Knowing whether there is influence of awareness, attitude, knowledge and tax sanctions on the tax compliance of MSME actors in the Ngemplak Region is the aim of conducting research. Multiple linear regression in the IBM SPSS Statistics v20 program was chosen as a technique for analyzing research data. The results of the study, namely taxpayer awareness and taxpayer knowledge have no significant effect on MSME taxpayer compliance in the Ngemplak Region. Taxpayer attitudes and tax sanctions have a significant effect on MSME taxpayer compliance in the Ngemplak Region.